2018
DOI: 10.3390/genes9120634
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Structure-Specific Endonucleases in Replication Stress

Abstract: Replication stress results in various forms of aberrant replication intermediates that need to be resolved for faithful chromosome segregation. Structure-specific endonucleases (SSEs) recognize DNA secondary structures rather than primary sequences and play key roles during DNA repair and replication stress. Holliday junction resolvase MUS81 (methyl methane sulfonate (MMS), and UV-sensitive protein 81) and XPF (xeroderma pigmentosum group F-complementing protein) are a subset of SSEs that resolve aberrant repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 160 publications
(263 reference statements)
0
11
0
Order By: Relevance
“…Excision of eccDNA requires two additional strand cleavages beyond the initiating DSB, and this is not a favoured outcome of intrachromosomal strand invasion ( Figure 6). Helicases such as Sgs1 will dissolve D-loops formed by strand invasion to minimise rearrangements during DSB repair [70], and the activity of structure specific endonuclease enzymes capable of cleaving the nicked Holliday Junctions in a D-loop is tightly restricted to G2/M (reviewed in [71]). Nonetheless, an endonuclease activity is required and we find Mus81, which has a strong preference for cleaving nicked Holliday Junction intermediates, to be critical for eccDNA formation.…”
Section: Discussionmentioning
confidence: 99%
“…Excision of eccDNA requires two additional strand cleavages beyond the initiating DSB, and this is not a favoured outcome of intrachromosomal strand invasion ( Figure 6). Helicases such as Sgs1 will dissolve D-loops formed by strand invasion to minimise rearrangements during DSB repair [70], and the activity of structure specific endonuclease enzymes capable of cleaving the nicked Holliday Junctions in a D-loop is tightly restricted to G2/M (reviewed in [71]). Nonetheless, an endonuclease activity is required and we find Mus81, which has a strong preference for cleaving nicked Holliday Junction intermediates, to be critical for eccDNA formation.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain genome stability and prevent unwanted DNA breaks, the activities of SSEs must be tightly coordinated with cell cycle and DNA damage response [3,4]. Previous studies showed that cell cycle kinases [72][73][74][75][76][77] and checkpoint kinases [17,74,78,79] play key roles in the regulation of SSEs.…”
Section: Discussionmentioning
confidence: 99%
“…Structure-specific endonucleases (SSEs) play crucial roles in the maintenance of genome stability by processing DNA intermediates during DNA replication, recombination, and repair [1,2]. Tight control of these nucleases is critical for accurately processing specific DNA structures without causing unnecessary DNA lesions [3,4]; however, the molecular mechanisms underlying the regulation of these nucleases have not been sufficiently revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the classic resolvase RuvC from bacteria [69], the eukaryotic HJ resolvases exhibit additional DNA debranching activities on DNA flap structures and DNA three-way junctions that are similar to RFs. Moreover, their actions are tightly regulated by post-translational modifications, protein–protein interactions and nucleocytoplasmic shuttling [70].…”
Section: Structure-specific Endonucleases: Substrate Spectrum Andmentioning
confidence: 99%